Consumers’ acceptance and valuation of healthier rice: implications for promoting healthy diets in the Philippines - Custodio, Marie Claire; Ynion, Jhoanne; Demont, Matty; De Steur, Hans (Emerald Publishing Limited, 2025)
Purpose This paper aims to analyze and compare consumers’ acceptance and valuation of brown, colored and low glycemic index rice and identify the factors that influence their willingness to pay (WTP). Design/methodology/approach A stated-preference survey was conducted among 600 middle-class urban consumers in the Philippines, using a contingent valuation approach with a between-subjects design. The data were analyzed using hierarchical multiple linear regression. Findings Consumers accepted healthier rice types, but they discounted them relative to premium white rice, despite receiving product-specific information on health benefits. Consumers’ household income, attitude toward healthy eating and their diet quality had significant effects on WTP. Snack occasions could serve as entry points for healthier rice rather than targeting the substitution of white rice during main eating occasions. Generic information on nutritional benefits of healthier rice products was insufficient to nudge consumers’ intentions toward integrating these products into their diets. Practical implications The empirical contribution provides insights for breeding programs on the design of rice target product profiles that incorporate nutritional attributes. Originality/value The current study addresses the gap in consumer preference studies by evaluating nutrition-related attributes of rice. Measures of attitude toward food-based dietary guidelines and indicators of diet quality were included in the set of predictors that may influence WTP. The results provide insights for designing nutrition education programs to promote healthier rice in the context of healthy eating habits and to enhance the health benefits of consumers’ current diets. Future studies should further explore different types of nutrition nudges that encourage consumers to eat healthier rice-based dishes and test nutrition communication strategies that move from a narrow product focus to a broader emphasis on dietary diversity by promoting healthier dishes based on healthier rice products.